Detection of Cryptosporidium Oocysts in Raw Meat in Misan City/ Iraq - Mohammed, Rawaa Ghanim (International Journal of Psychosocial Rehabilitation, 2020)
Background: Intestinal parasites are widespread in developing countries. Cryptosporidium has appeared to be one of the most common parasites. The study aimed to detect the contamination of raw meat with Cryptosporidium oocyst in Misan city and elevate most type of contaminated meat. Materials and Methods: This study was done from September 2017 to May 2018, 60 samples of meat (30 beef and 30 sheep) 90 from meat product samples. Results: The study showed that contamination percentage of (60) raw meat ;30 from cattle and 30 from sheep; reached 6.7 % and 3.33% in cattle and sheep respectively with high prevalence contamination in meat of cattle. Sausages samples recorded higher contamination rate (10% ) than hamburger and luncheon (6.7%) and (3.4%) respectively. Conclusions: The present study reported the detection of Cryptosporidium oocysts in meat and meat products and there is possibility of transmission of oocysts to human during consumption. The results of our study clarify that contamination of meat products may be occurred during preparation, since sausage and hamburger do not exposed to heat completely during preparation